Interleukin-34 as a Robust Predictor of No-Reflow Phenomenon in ST-Elevation Myocardial Infarction: Insights into Inflammatory Mechanisms and Clinical Implications - Mehdi Karasu; Hasan Ata Bolayır; İbrahim Aktaş (Gazi Medical Journal)
Objective: ST-elevation myocardial infarction (STEMI) poses a significant challenge despite advances in reperfusion strategies. The “no-reflow” phenomenon, characterized by inadequate microvascular blood flow restoration following successful revascularization, remains poorly understood. Inflammation, particularly interleukin-34 (IL-34), is implicated in cardiovascular disease, prompting investigation into its role in no-reflow. Methods: This observational study included 182 patients with STEMI (32 with no-reflow, 150 without) and 100 controls. Clinical and angiographic data were analyzed, and IL-34 levels were measured. Logistic regression and receiver operating characteristic (ROC) analysis assessed IL-34’s predictive value for no-reflow. Results: Patients with no reflow exhibited elevated IL-34 levels compared with controls and those without no-reflow. Logistic regression identified IL-34 as an independent predictor of no-reflow (odds ratio: 1,020, p<0.001). ROC analysis showed IL-34’s significant predictive value (area under the curve: 0.972, p<0.001). Conclusion: IL-34 emerges as a robust predictor of no-reflow in STEMI, potentially reflecting its role in macrophage activation and the inflammatory response. These findings suggest a novel avenue for understanding and mitigating no-reflow in STEMI, paving the way for targeted therapies. Early identification of high-risk patients could inform tailored interventions, ultimately improving STEMI outcomes. Further research is warranted to elucidate IL-34’s mechanistic involvement and validate its predictive value in larger cohorts.